Applying Choice Architecture and Marketing Pre-Suasion to the Motorcycle Industry - Landis, Bethany; Lemay, Stephen A.; McMahon, Dave (Journal of Marketing Development and Competitiveness, 2021)
In this analysis, we examine the motorcycle industry in terms of Cialdini’s concept of Pre- Suasion. We use the chapter titles from the book to explore how these concepts could or should help the motorcycle industry adapt to shifts in its markets, shifts that are both demographic and cultural. In the process, we also explore ideas like product gentrification and choice architecture, ideas at the heart of the motorcycle marketing problem. We conclude that motorcycle promotions and messaging lack traction with younger buyers. We close with an extensive list of questions calling for further research.